SU(2) slave fermion solution of the Kitaev honeycomb lattice model - Burnell, F; Nayak, C (2011)
We apply the SU(2) slave fermion formalism to the Kitaev honeycomb lattice model. We show that both the toric code phase (the A phase) and the gapless phase of this model (the B phase) can be identified with p-wave superconducting phases of the slave fermions, with nodal lines which, respectively, do not or do intersect the Fermi surface. The non-Abelian Ising anyon phase is a p+ip superconducting phase that occurs when the B phase is subjected to a gap-opening magnetic field. We also discuss the transitions between these phases in this language. © 2011 American Physical Society.